2021
DOI: 10.1111/jssr.12720
|View full text |Cite
|
Sign up to set email alerts
|

Religion Protected Mental Health but Constrained Crisis Response During Crucial Early Days of the COVID‐19 Pandemic

Abstract: This study demonstrates that religion protected mental health but constrained support for crisis response during the crucial early days of the COVID-19 pandemic. Data from a national probability-based sample of the U.S. population show that highly religious individuals and evangelicals suffered less distress in March 2020. They were also less likely to see the coronavirus outbreak as a crisis and less likely to support public health restrictions to limit the spread of the virus. The conservative politicization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“… 2021 ; Gonzalez et al. 2021 ; Hao and Shao 2021 ; Perry, Whitehead, and Grubbs 2020 ; Pew Research Center 2020 ; Schnabel and Schieman 2021 ). Religiosity is associated with perceptions of governmental and scientific authority (Chan 2018 ; Payir et al.…”
Section: Religion and Medically Recommended Responses To Covid‐19mentioning
confidence: 99%
“… 2021 ; Gonzalez et al. 2021 ; Hao and Shao 2021 ; Perry, Whitehead, and Grubbs 2020 ; Pew Research Center 2020 ; Schnabel and Schieman 2021 ). Religiosity is associated with perceptions of governmental and scientific authority (Chan 2018 ; Payir et al.…”
Section: Religion and Medically Recommended Responses To Covid‐19mentioning
confidence: 99%
“…Sociologists and anthropologists of religion turned to examine the ways different religious communities follow social distance guidelines (DeFranza et al 2020;Taragin-Zeller et al 2020;Goren et al 2021;Schnabel and Schieman 2021). Perry, Whitehead, and Grubbs found that in the US, the left were more likely to recommended precautions, while those on the (religious) right were more likely to disregard recommended precautions (Perry et al 2020).…”
Section: Religion Change and Covid-19mentioning
confidence: 99%
“…Responses to the pandemic, the sacrifices to normalcy needed to curb it, and even whether it was a real threat to be concerned about were quickly politicized by politicians, pundits, and the public alike [ 14 18 ]. Emerging research on partisanship and the pandemic in the United States demonstrates vastly different responses and approaches to whether the pandemic is real, something to stress about, and important enough to make a person limit their in-person connections, disrupt their routine, and constrain their daily life up to and including isolation [ 15 , 17 , 19 – 21 ]. It is possible, therefore, that although a widespread pandemic presumably exposes everyone to generally similar stressors, partisanship may cause people to experience and respond to those stressors quite differently.…”
Section: Introductionmentioning
confidence: 99%